From The History of Early Banks and Their Development - R. N, Tukhtayeva; N. U, Tosheva (Indonesian Journal Publisher, 2025)
This article explores the history of the emergence and development of early Banks. The article analyzes the stages of formation of the banking system from ancient times to the present day, the initial banking operations, their economic and social role. The geographical distribution, main features and specific aspects of the activities of early banks are considered. Important historical events and processes that influenced the development of the banking system are also highlighted. The article is intended for the masses of researchers, students and a wide range of readers interested in the history of banking.